Panel Reports—New Worlds, New Horizons in Astronomy and Astrophysics - National Research Council (The National Academies Press, 2011)
Every 10 years the National Research Council releases a survey of astronomy and astrophysics outlining priorities for the coming decade. The most recent survey, titled New Worlds, New Horizons in Astronomy and Astrophysics, provides overall priorities and recommendations for the field as a whole based on a broad and comprehensive examination of scientific opportunities, infrastructure, and organization in a national and international context. Panel Reports—New Worlds, New Horizons in Astronomy and Astrophysics is a collection of reports, each of which addresses a key sub-area of the field, prepared by specialists in that subarea, and each of which played an important role in setting overall priorities for the field. The collection, published in a single volume, includes the reports of the following panels: Cosmology and Fundamental Physics Galaxies Across Cosmic Time The Galactic Neighborhood Stars and Stellar Evolution Planetary Systems and Star Formation Electromagnetic Observations from Space Optical and Infrared Astronomy from the Ground Particle Astrophysics and Gravitation Radio, Millimeter, and Submillimeter Astronomy from the Ground The Committee for a Decadal Survey of Astronomy and Astrophysics synthesized these reports in the preparation of its prioritized recommendations for the field as a whole. These reports provide additional depth and detail in each of their respective areas. Taken together, they form an essential companion volume to New Worlds, New Horizons: A Decadal Survey of Astronomy and Astrophysics. The book of panel reports will be useful to managers of programs of research in the field of astronomy and astrophysics, the Congressional committees with jurisdiction over the agencies supporting this research, the scientific community, and the public.
Keywords: Space and Aeronautics

New Worlds, New Horizons: A Midterm Assessment - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
New Worlds, New Horizons in Astronomy and Astrophysics (NWNH), the report of the 2010 decadal survey of astronomy and astrophysics, put forward a vision for a decade of transformative exploration at the frontiers of astrophysics. This vision included mapping the first stars and galaxies as they emerge from the collapse of dark matter and cold clumps of hydrogen, finding new worlds in a startlingly diverse population of extrasolar planets, and exploiting the vastness and extreme conditions of the universe to reveal new information about the fundamental laws of nature. NWNH outlined a compelling program for understanding the cosmic order and for opening new fields of inquiry through the discovery areas of gravitational waves, time-domain astronomy, and habitable planets. Many of these discoveries are likely to be enabled by cyber-discovery and the power of mathematics, physics, and imagination. To help realize this vision, NWNH recommended a suite of innovative and powerful facilities, along with balanced, strong support for the scientific community engaged in theory, data analysis, technology development, and measurements with existing and new instrumentation. Already in the first half of the decade, scientists and teams of scientists working with these cutting-edge instruments and with new capabilities in data collection and analysis have made spectacular discoveries that advance the NWNH vision. New Worlds, New Horizons: A Midterm Assessment reviews the responses of NASA's Astrophysics program, NSF's Astronomy program, and DOE's Cosmic Frontiers program to NWNH. This report describes the most significant scientific discoveries, technical advances, and relevant programmatic changes in astronomy and astrophysics over the years since the publication of the decadal survey, and assesses how well the Agencies' programs address the strategies, goals, and priorities outlined in the 2010 decadal survey.
Keywords: Space and Aeronautics

New Worlds, New Horizons in Astronomy and Astrophysics - National Research Council (The National Academies Press, 2010)
Driven by discoveries, and enabled by leaps in technology and imagination, our understanding of the universe has changed dramatically during the course of the last few decades. The fields of astronomy and astrophysics are making new connections to physics, chemistry, biology, and computer science. Based on a broad and comprehensive survey of scientific opportunities, infrastructure, and organization in a national and international context, New Worlds, New Horizons in Astronomy and Astrophysics outlines a plan for ground- and space- based astronomy and astrophysics for the decade of the 2010's. Realizing these scientific opportunities is contingent upon maintaining and strengthening the foundations of the research enterprise including technological development, theory, computation and data handling, laboratory experiments, and human resources. New Worlds, New Horizons in Astronomy and Astrophysics proposes enhancing innovative but moderate-cost programs in space and on the ground that will enable the community to respond rapidly and flexibly to new scientific discoveries. The book recommends beginning construction on survey telescopes in space and on the ground to investigate the nature of dark energy, as well as the next generation of large ground-based giant optical telescopes and a new class of space-based gravitational observatory to observe the merging of distant black holes and precisely test theories of gravity. New Worlds, New Horizons in Astronomy and Astrophysics recommends a balanced and executable program that will support research surrounding the most profound questions about the cosmos. The discoveries ahead will facilitate the search for habitable planets, shed light on dark energy and dark matter, and aid our understanding of the history of the universe and how the earliest stars and galaxies formed. The book is a useful resource for agencies supporting the field of astronomy and astrophysics, the Congressional committees with jurisdiction over those agencies, the scientific community, and the public.
Keywords: Space and Aeronautics

Pathways to Discovery in Astronomy and Astrophysics for the 2020s - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
We live in a time of extraordinary discovery and progress in astronomy and astrophysics. The next decade will transform our understanding of the universe and humanity's place in it. Every decade the U.S. agencies that provide primary federal funding for astronomy and astrophysics request a survey to assess the status of, and opportunities for the Nation's efforts to forward our understanding of the cosmos. Pathways to Discovery in Astronomy and Astrophysics for the 2020s identifies the most compelling science goals and presents an ambitious program of ground- and space-based activities for future investment in the next decade and beyond. The decadal survey identifies three important science themes for the next decade aimed at investigating Earth-like extrasolar planets, the most energetic processes in the universe, and the evolution of galaxies. The Astro2020 report also recommends critical near-term actions to support the foundations of the profession as well as the technologies and tools needed to carry out the science.
Keywords: Space and Aeronautics

Severe Space Weather Events: Understanding Societal and Economic Impacts: A Workshop Report - National Research Council (The National Academies Press, 2008)
The adverse effects of extreme space weather on modern technology--power grid outages, high-frequency communication blackouts, spacecraft anomalies--are well known and well documented, and the physical processes underlying space weather are also generally well understood. Less well documented and understood, however, are the potential economic and societal impacts of the disruption of critical technological systems by severe space weather. As a first step toward determining the socioeconomic impacts of extreme space weather events and addressing the questions of space weather risk assessment and management, a public workshop was held in May 2008. The workshop brought together representatives of industry, the government, and academia to consider both direct and collateral effects of severe space weather events, the current state of the space weather services infrastructure in the United States, the needs of users of space weather data and services, and the ramifications of future technological developments for contemporary society's vulnerability to space weather. The workshop concluded with a discussion of un- or underexplored topics that would yield the greatest benefits in space weather risk management.
Keywords: Space and Aeronautics

Solar and Space Physics: A Science for a Technological Society - National Research Council (The National Academies Press, 2013)
From the interior of the Sun, to the upper atmosphere and near-space environment of Earth, and outward to a region far beyond Pluto where the Sun's influence wanes, advances during the past decade in space physics and solar physics—the disciplines NASA refers to as heliophysics—have yielded spectacular insights into the phenomena that affect our home in space. Solar and Space Physics, from the National Research Council's (NRC's) Committee for a Decadal Strategy in Solar and Space Physics, is the second NRC decadal survey in heliophysics. Building on the research accomplishments realized during the past decade, the report presents a program of basic and applied research for the period 2013-2022 that will improve scientific understanding of the mechanisms that drive the Sun's activity and the fundamental physical processes underlying near-Earth plasma dynamics, determine the physical interactions of Earth's atmospheric layers in the context of the connected Sun-Earth system, and enhance greatly the capability to provide realistic and specific forecasts of Earth's space environment that will better serve the needs of society. Although the recommended program is directed primarily at NASA and the National Science Foundation for action, the report also recommends actions by other federal agencies, especially the parts of the National Oceanic and Atmospheric Administration charged with the day-to-day (operational) forecast of space weather. In addition to the recommendations included in this summary, related recommendations are presented in this report.
Keywords: Space and Aeronautics; Math, Chemistry, and Physics

Vision and Voyages for Planetary Science in the Decade 2013-2022 - National Research Council (The National Academies Press, 2011)
In recent years, planetary science has seen a tremendous growth in new knowledge. Deposits of water ice exist at the Moon's poles. Discoveries on the surface of Mars point to an early warm wet climate, and perhaps conditions under which life could have emerged. Liquid methane rain falls on Saturn's moon Titan, creating rivers, lakes, and geologic landscapes with uncanny resemblances to Earth's. Vision and Voyages for Planetary Science in the Decade 2013-2022 surveys the current state of knowledge of the solar system and recommends a suite of planetary science flagship missions for the decade 2013-2022 that could provide a steady stream of important new discoveries about the solar system. Research priorities defined in the report were selected through a rigorous review that included input from five expert panels. NASA's highest priority large mission should be the Mars Astrobiology Explorer Cacher (MAX-C), a mission to Mars that could help determine whether the planet ever supported life and could also help answer questions about its geologic and climatic history. Other projects should include a mission to Jupiter's icy moon Europa and its subsurface ocean, and the Uranus Orbiter and Probe mission to investigate that planet's interior structure, atmosphere, and composition. For medium-size missions, Vision and Voyages for Planetary Science in the Decade 2013-2022 recommends that NASA select two new missions to be included in its New Frontiers program, which explores the solar system with frequent, mid-size spacecraft missions. If NASA cannot stay within budget for any of these proposed flagship projects, it should focus on smaller, less expensive missions first. Vision and Voyages for Planetary Science in the Decade 2013-2022 suggests that the National Science Foundation expand its funding for existing laboratories and establish new facilities as needed. It also recommends that the program enlist the participation of international partners. This report is a vital resource for government agencies supporting space science, the planetary science community, and the public.
Keywords: Space and Aeronautics

Pathways to Exploration: Rationales and Approaches for a U.S. Program of Human Space Exploration - National Research Council (The National Academies Press, 2014)
The United States has publicly funded its human spaceflight program on a continuous basis for more than a half-century, through three wars and a half-dozen recessions, from the early Mercury and Gemini suborbital and Earth orbital missions, to the lunar landings, and thence to the first reusable winged crewed spaceplane that the United States operated for three decades. Today the United States is the major partner in a massive orbital facility - the International Space Station - that is becoming the focal point for the first tentative steps in commercial cargo and crewed orbital space flights. And yet, the long-term future of human spaceflight beyond this project is unclear. Pronouncements by multiple presidents of bold new ventures by Americans to the Moon, to Mars, and to an asteroid in its native orbit, have not been matched by the same commitment that accompanied President Kennedy's now fabled 1961 speech-namely, the substantial increase in NASA funding needed to make it happen. Are we still committed to advancing human spaceflight? What should a long-term goal be, and what does the United States need to do to achieve it? Pathways to Exploration explores the case for advancing this endeavor, drawing on the history of rationales for human spaceflight, examining the attitudes of stakeholders and the public, and carefully assessing the technical and fiscal realities. This report recommends maintaining the long-term focus on Mars as the horizon goal for human space exploration. With this goal in mind, the report considers funding levels necessary to maintain a robust tempo of execution, current research and exploration projects and the time/resources needed to continue them, and international cooperation that could contribute to the achievement of spaceflight to Mars. According to Pathways to Exploration, a successful U.S. program would require sustained national commitment and a budget that increases by more than the rate of inflation. In reviving a U.S. human exploration program capable of answering the enduring questions about humanity's destiny beyond our tiny blue planet, the nation will need to grapple with the attitudinal and fiscal realities of the nation today while staying true to a small but crucial set of fundamental principles for the conduct of exploration of the endless frontier. The recommendations of Pathways to Exploration provide a clear map toward a human spaceflight program that inspires students and citizens by furthering human exploration and discovery, while taking into account the long-term commitment necessary to achieve this goal.
Keywords: Space and Aeronautics

The Space Science Decadal Surveys: Lessons Learned and Best Practices - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The National Research Council has conducted 11 decadal surveys in the Earth and space sciences since 1964 and released the latest four surveys in the past 8 years. The decadal surveys are notable in their ability to sample thoroughly the research interest, aspirations, and needs of a scientific community. Through a rigorous process, a primary survey committee and thematic panels of community members construct a prioritized program of science goals and objectives and define an executable strategy for achieving them. These reports play a critical role in defining the nation's agenda in that science area for the following 10 years, and often beyond. The Space Science Decadal Surveys considers the lessons learned from previous surveys and presents options for possible changes and improvements to the process, including the statement of task, advanced preparation, organization, and execution. This report discusses valuable aspects of decadal surveys that could taken further, as well as some challenges future surveys are likely to face in searching for the richest areas of scientific endeavor, seeking community consensus of where to go next, and planning how to get there. The Space Science Decadal Surveys describes aspects in the decadal survey prioritization process, including balance in the science program and across the discipline; balance between the needs of current researchers and the development of the future workforce; and balance in mission scale - smaller, competed programs versus large strategic missions.
Keywords: Space and Aeronautics

Optimizing the U.S. Ground-Based Optical and Infrared Astronomy System - National Research Council (The National Academies Press, 2015)
New astronomical facilities, such as the under-construction Large Synoptic Survey Telescope and planned 30-meter-class telescopes, and new instrumentation on existing optical and infrared (OIR) telescopes, hold the promise of groundbreaking research and discovery. How can we extract the best science from these and other astronomical facilities in an era of potentially flat federal budgets for both the facilities and the research grants? Optimizing the U.S. Ground-Based Optical and Infrared Astronomy System provides guidance for these new programs that align with the scientific priorities and the conclusions and recommendations of two National Research Council (NRC) decadal surveys, New Worlds, New Horizons for Astronomy and Astrophysics and Vision and Voyages for Planetary Sciences in the Decade 2013-2022, as well as other NRC reports. This report describes a vision for a U.S. OIR System that includes a telescope time exchange designed to enhance science return by broadening access to capabilities for a diverse community, an ongoing planning process to identify and construct next generation capabilities to realize decadal science priorities, and near-term critical coordination, planning, and instrumentation needed to usher in the era of LSST and giant telescopes.
Keywords: Space and Aeronautics

Earth Science and Applications from Space: National Imperatives for the Next Decade and Beyond - National Research Council (The National Academies Press, 2007)
Natural and human-induced changes in Earth's interior, land surface, biosphere, atmosphere, and oceans affect all aspects of life. Understanding these changes requires a range of observations acquired from land-, sea-, air-, and space-based platforms. To assist NASA, NOAA, and USGS in developing these tools, the NRC was asked to carry out a "decadal strategy" survey of Earth science and applications from space that would develop the key scientific questions on which to focus Earth and environmental observations in the period 2005-2015 and beyond, and present a prioritized list of space programs, missions, and supporting activities to address these questions. This report presents a vision for the Earth science program; an analysis of the existing Earth Observing System and recommendations to help restore its capabilities; an assessment of and recommendations for new observations and missions for the next decade; an examination of and recommendations for effective application of those observations; and an analysis of how best to sustain that observation and applications system.
Keywords: Earth Sciences; Space and Aeronautics

Searching for Life Across Space and Time: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The search for life is one of the most active fields in space science and involves a wide variety of scientific disciplines, including planetary science, astronomy and astrophysics, chemistry, biology, chemistry, and geoscience. In December 2016, the Space Studies Board hosted a workshop to explore the possibility of habitable environments in the solar system and in exoplanets, techniques for detecting life, and the instrumentation used. This publication summarizes the presentations and discussions from the workshop.
Keywords: Space and Aeronautics

Preparing for the High Frontier: The Role and Training of NASA Astronauts in the Post-Space Shuttle Era - National Research Council (The National Academies Press, 2011)
As the National Aeronautics and Space Administration (NASA) retires the Space Shuttle and shifts involvement in International Space Station (ISS) operations, changes in the role and requirements of NASA's Astronaut Corps will take place. At the request of NASA, the National Research Council (NRC) addressed three main questions about these changes: what should be the role and size of Johnson Space Center's (JSC) Flight Crew Operations Directorate (FCOD); what will be the requirements of astronaut training facilities; and is the Astronaut Corps' fleet of training aircraft a cost-effective means of preparing astronauts for NASA's spaceflight program? This report presents an assessment of several issues driven by these questions. This report does not address explicitly the future of human spaceflight.
Keywords: Space and Aeronautics

The Limits of Organic Life in Planetary Systems - National Research Council (The National Academies Press, 2007)
The search for life in the solar system and beyond has to date been governed by a model based on what we know about life on Earth (terran life). Most of NASA's mission planning is focused on locations where liquid water is possible and emphasizes searches for structures that resemble cells in terran organisms. It is possible, however, that life exists that is based on chemical reactions that do not involve carbon compounds, that occurs in solvents other than water, or that involves oxidation-reduction reactions without oxygen gas. To assist NASA incorporate this possibility in its efforts to search for life, the NRC was asked to carry out a study to evaluate whether nonstandard biochemistry might support life in solar system and conceivable extrasolar environments, and to define areas to guide research in this area. This book presents an exploration of a limited set of hypothetical chemistries of life, a review of current knowledge concerning key questions or hypotheses about nonterran life, and suggestions for future research.
Keywords: Space and Aeronautics

Powering Science: NASA's Large Strategic Science Missions - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
NASA's Science Mission Directorate (SMD) currently operates over five dozen missions, with approximately two dozen additional missions in development. These missions span the scientific fields associated with SMD's four divisions—Astrophysics, Earth Science, Heliophysics, and Planetary Sciences. Because a single mission can consist of multiple spacecraft, NASA-SMD is responsible for nearly 100 operational spacecraft. The most high profile of these are the large strategic missions, often referred to as "flagships." Large strategic missions are essential to maintaining the global leadership of the United States in space exploration and in science because only the United States has the budget, technology, and trained personnel in multiple scientific fields to conduct missions that attract a range of international partners. This report examines the role of large, strategic missions within a balanced program across NASA-SMD space and Earth sciences programs. It considers the role and scientific productivity of such missions in advancing science, technology and the long-term health of the field, and provides guidance that NASA can use to help set the priority of larger missions within a properly balanced program containing a range of mission classes.
Keywords: Space and Aeronautics

Recapturing a Future for Space Exploration: Life and Physical Sciences Research for a New Era - National Research Council (The National Academies Press, 2011)
More than four decades have passed since a human first set foot on the Moon. Great strides have been made in our understanding of what is required to support an enduring human presence in space, as evidenced by progressively more advanced orbiting human outposts, culminating in the current International Space Station (ISS). However, of the more than 500 humans who have so far ventured into space, most have gone only as far as near-Earth orbit, and none have traveled beyond the orbit of the Moon. Achieving humans' further progress into the solar system had proved far more difficult than imagined in the heady days of the Apollo missions, but the potential rewards remain substantial. During its more than 50-year history, NASA's success in human space exploration has depended on the agency's ability to effectively address a wide range of biomedical, engineering, physical science, and related obstacles—an achievement made possible by NASA's strong and productive commitments to life and physical sciences research for human space exploration, and by its use of human space exploration infrastructures for scientific discovery. The Committee for the Decadal Survey of Biological and Physical Sciences acknowledges the many achievements of NASA, which are all the more remarkable given budgetary challenges and changing directions within the agency. In the past decade, however, a consequence of those challenges has been a life and physical sciences research program that was dramatically reduced in both scale and scope, with the result that the agency is poorly positioned to take full advantage of the scientific opportunities offered by the now fully equipped and staffed ISS laboratory, or to effectively pursue the scientific research needed to support the development of advanced human exploration capabilities. Although its review has left it deeply concerned about the current state of NASA's life and physical sciences research, the Committee for the Decadal Survey on Biological and Physical Sciences in Space is nevertheless convinced that a focused science and engineering program can achieve successes that will bring the space community, the U.S. public, and policymakers to an understanding that we are ready for the next significant phase of human space exploration. The goal of this report is to lay out steps and develop a forward-looking portfolio of research that will provide the basis for recapturing the excitement and value of human spaceflight—thereby enabling the U.S. space program to deliver on new exploration initiatives that serve the nation, excite the public, and place the United States again at the forefront of space exploration for the global good.
Keywords: Space and Aeronautics

Exoplanet Science Strategy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The past decade has delivered remarkable discoveries in the study of exoplanets. Hand-in-hand with these advances, a theoretical understanding of the myriad of processes that dictate the formation and evolution of planets has matured, spurred on by the avalanche of unexpected discoveries. Appreciation of the factors that make a planet hospitable to life has grown in sophistication, as has understanding of the context for biosignatures, the remotely detectable aspects of a planet's atmosphere or surface that reveal the presence of life. Exoplanet Science Strategy highlights strategic priorities for large, coordinated efforts that will support the scientific goals of the broad exoplanet science community. This report outlines a strategic plan that will answer lingering questions through a combination of large, ambitious community-supported efforts and support for diverse, creative, community-driven investigator research.
Keywords: Space and Aeronautics

Space Nuclear Propulsion for Human Mars Exploration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Space Nuclear Propulsion for Human Mars Exploration identifies primary technical and programmatic challenges, merits, and risks for developing and demonstrating space nuclear propulsion technologies of interest to future exploration missions. This report presents key milestones and a top-level development and demonstration roadmap for performance nuclear thermal propulsion and nuclear electric propulsion systems and identifies missions that could be enabled by successful development of each technology.
Keywords: Space and Aeronautics